Photovoltaic powered electric vehicle using PMSM drive scheme. (1st January 2013) - Sharma, Deepali; Gaur, Prerna; Mittal, A.P.; Singh, Bhim
In this paper, a Photovoltaic (PV) array and battery-powered Permanent Magnet Synchronous Motor (PMSM) drive scheme, along with the design aspects of Electric Vehicles (EVs) and solar cells, is presented. EVs provide a potential solution to the problem of dependence on ever decreasing and polluting fossil fuels for the transportation sector. PMSM is chosen to be the motor for a four-wheel drive EV owing to its various inherent advantages. PMSM is fed from a PV source along with the battery to provide a further contribution towards solution to the problems of fossil fuels depletion, global warming and climate change. Results for speed and torque tracking by the proposed vehicle in various driving modes are presented.